A gene activated in mouse 3T3 cells by serum growth factors encodes a protein with "zinc finger" sequences. - Christy, B A (1988)
We have recently identified by cDNA cloning a set of genes that are rapidly activated in mouse 3T3 cells by serum or purified growth factors. Here we report that the cDNA (clone 268) derived from one of these immediate early genes (zif/268) encodes a protein with three tandem "zinc finger" sequences typical of a class of eukaryotic transcription factors. The mRNA of zif/268 is present in many organs and tissues of the mouse and is especially abundant in the brain and thymus tissue. The 5' genomic flanking sequence of zif/268 has sequences related to binding sites for known regulatory proteins, including four sequences that resemble the core of the serum response elements (SREs) upstream of the c-fos and actin genes. The SRE-like sequences could be responsible for the coordinate activation of zif/268 and fos after serum stimulation of 3T3 cells.